Development of Android-Based Let's-Teach Learning Media in Physical Education Learning Curriculum 13 (Journal of Physical Education and Sports, 2022)
The development of science and technology has a significant impact on human lifestyles, which must likewise evolve. This study aims to: (1) analyze the development of Android-based Let's-Teach learning media on smartphones for PE (Physical Education) learning documents for grade XI; (2) analyze the effectiveness of applications for developing Android-based learning media and teacher administration in PE learning for grade XI; and (3) analyze the level of feasibility of using Android-based learning media for PE learning materials for grade XI. This research used development research. Potential and problems, data collection, product design, design validation, usage test, product revision, trial run, design revision, product revision, and mass production are the 10 phases of the used development approach. Data collection used product validation questionnaires, respondent questionnaires and documentation. This study's data analysis method included descriptive percentages. The result of this study was an Android-based PE learning resource for high school Grade XI. Small-scale testing of the PE learning media application for high school Grade XI yielded a score of 91 percent, which is regarded as very good. The results of the large-scale trial of the high school PE learning media application were 94 percent very good, indicating that this application could be mass-produced and utilized by teachers for high school PE learning media. It was determined that a product in the form of an Android-based pE learning media could be mass-produced and used to support the education of high school PE teachers.